Analysis of The Relationship Between The Implementation of The Behavior-Based Safety (BBS) Program and The Level of Employee Compliance With Occupational Safety Principles at PT. Angkasa Pura Logistics - Firdaus, Mochamad David Maulana; Novrizal, Ahmad; Ramadhan, Raihan Aliffathur; Irfan, Mochammad; Ariyakohir, Muhammad; Abizarga, Daffa Qhalby; Oroh, Valentino Rifai; Malik, Anis Rohmana (Jurnal Multidisiplin Indonesia, 2024)
Based on data from the Ministry of Manpower (MoM) in 2023, the number of workplace accidents in Indonesia was recorded at 370,747 cases. The Behavior-Based Safety (BBS) program is an approach that focuses on human behavior and social relationships in the workplace. Its goal is to reduce the risk of accidents and work-related injuries by increasing awareness, involvement, and responsibility of employees towards their own safety and the safety of their colleagues. The research was conducted using a quantitative cross-sectional research method. Data collected provide an overview of the relationship between variables. A cross-sectional research design was used to collect data on the Behavior-Based Safety (BBS) program, the level of compliance with work safety behaviors, and work safety behaviors at PT. Angkasa Pura Logistics at a specific time. Data were collected using a questionnaire filled out by respondents. The variation in compliance level scores can be explained by 22.5% of the variation in BBS program scores, while the remaining 77.5% is explained by variation in other variables outside the research model. The variation in employee work safety behavior scores can be explained by 66.4% of the variation in BBS program scores and compliance level, while the remaining 33.6% is explained by variation in other variables outside the research model. There is a significant and meaningful relationship between the BBS program and compliance level. There is a significant and meaningful relationship between the BBS program and work safety behavior. There is a significant and meaningful relationship between compliance level and work safety behavior. There is a direct relationship between the BBS program and workplace safety behavior. Therefore, the Compliance Level intervening variable does not mediate the relationship between the BBS Program and Work Safety Behavior.